Pendampingan Belajar pada Anak Usia Sekolah Dasar untuk Meningkatkan Prestasi dan Motivasi Belajar di Desa Tanjung Putus, Padang Tualang, Langkat, Sumatera Utara - Saputri, Lilis; Mardiati, Mardiati; Sitepu, Dewi Rulia Br; Susilawati, Enny; Ningsih, Yulia; Ayumi, Nadia; Siregar, Zulfy Aswita Dewi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The community service program aims to: 1) improve the learning achievement of elementary school-age children; 2) increase the learning motivation of elementary school-age children; and 3) help parents pay more attention to their children while they are studying in Tanjung Putus Village. Formal community service activities are carried out by making study assistance available through tutoring. The subjects of the service are elementary school-age children and their parents. Implementation of activities through several stages, namely planning, observation, implementation of technical implementation, program implementation, and evaluation. The results of community service obtained have succeeded in: 1) increasing the learning achievement abilities of elementary school-age children; 2) increasing the learning motivation of elementary school-age children; and 3) helping parents pay more attention to their children's studies in Tanjung Putus Village.